2017
DOI: 10.1515/hmbci-2016-0053
|View full text |Cite
|
Sign up to set email alerts
|

Expression, purification and characterization of human cytosolic sulfotransferase (SULT) 1C4

Abstract: Human cytosolic sulfotransferase 1C4 (hSULT1C4) is a dimeric Phase II drug-metabolizing enzyme primarily expressed in the developing fetus. SULTs facilitate the transfer of a hydrophilic sulfonate moiety from 3′-phosphoadenosine-5′-phosphosulfate (PAPS) onto an acceptor substrate altering the substrate’s biological activity and increasing the compound’s water solubility. While several of the hSULTs’ endogenous and xenobiotic substrates have been identified, the physiological function of hSULT1C4 remains unknow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…Herein, genistein-7-glucoside has a higher affinity for β-glucosidase than quercetin-4′-glucoside thus the former shows a higher deglycosylation rate, whereas some other glycosides such as quercetin-3,4′-diglucoside, quercetin-3-glucoside, kaempferol-3-glucoside, quercetin-3-rhamnoglucoside, and naringenin-7-rhamnoglucoside prefer to remain unchanged (Day et al, 1998). This intracellular reaction is regarded as a vital way to expose hydroxyl group of xenobiotics for further conjugation Cheng et al (1999), Margaillan et al (2015), Wong et al (2009), Finel et al (2005), King et al (1999), Mostaghel et al (2016), King et al (2000), Teubner et al (2007), Cheng et al (1998), Cheng et al (1999), Barbier et al (2000), Knights et al (2013), Chimalakonda et al (2011), Riches et al (2009), Ghosh et al (2013), Sakamoto et al (2015), Lu et al (2015), Guidry et al (2017), Kurogi et al (2017),…”
Section: Phase II Metabolism In Enterocytesmentioning
confidence: 99%
“…Herein, genistein-7-glucoside has a higher affinity for β-glucosidase than quercetin-4′-glucoside thus the former shows a higher deglycosylation rate, whereas some other glycosides such as quercetin-3,4′-diglucoside, quercetin-3-glucoside, kaempferol-3-glucoside, quercetin-3-rhamnoglucoside, and naringenin-7-rhamnoglucoside prefer to remain unchanged (Day et al, 1998). This intracellular reaction is regarded as a vital way to expose hydroxyl group of xenobiotics for further conjugation Cheng et al (1999), Margaillan et al (2015), Wong et al (2009), Finel et al (2005), King et al (1999), Mostaghel et al (2016), King et al (2000), Teubner et al (2007), Cheng et al (1998), Cheng et al (1999), Barbier et al (2000), Knights et al (2013), Chimalakonda et al (2011), Riches et al (2009), Ghosh et al (2013), Sakamoto et al (2015), Lu et al (2015), Guidry et al (2017), Kurogi et al (2017),…”
Section: Phase II Metabolism In Enterocytesmentioning
confidence: 99%
“…These data show that SULT1A1, SULT1C2, SULT1E1, and SULT2A1 mRNA and protein are substantially expressed in prenatal liver, whereas SULT1C4 is substantially expressed only at the mRNA level. SULT1C4 was recently shown to metabolize estrogenic compounds, including estradiol and environmental estrogens (Guidry et al, 2017). Although hepatic expression of the SULT1C genes and SULT1E1 decreases during the transition from fetal to adult life, SULT1A1 expression stays relatively constant whereas SULT2A1 expression increases.…”
mentioning
confidence: 99%
“…SULT1C4 is a member of a gene subfamily that includes three human members, SULT1C2,1C3, and 1C4. Several studies have suggested that SULT1C4 has the highest sulfonation capacity of the SULT1C enzymes towards xenobiotics, including a wide range of drugs (e.g., acetaminophen), environmental chemicals (e.g., bisphenol A), and procarcinogens (e.g., hydroxymethyl furans) (Sakakibara et al, 1998;Glatt et al, 2004;Allali-Hassani et al, 2007;Yasuda et al, 2007;Glatt et al, 2012;Yamamoto et al, 2015;Yamamoto et al, 2016;Guidry et al, 2017;Rasool et al, 2017). SULT1C4 is also capable of metabolizing estrogenic compounds, such as catechol and methoxy estrogens (Allali-Hassani et al, 2007;Hui et al, 2008).…”
Section: Downloaded Frommentioning
confidence: 99%
“…SULT1C4 is also capable of metabolizing estrogenic compounds, such as catechol and methoxy estrogens (Allali-Hassani et al, 2007;Hui et al, 2008). Guidry et al (Guidry et al, 2017) recently reported that SULT1C4 has high sulfonation capacity towards dietary flavonoids and environmental estrogens.…”
Section: Downloaded Frommentioning
confidence: 99%
See 1 more Smart Citation